2015
DOI: 10.1111/jomf.12178
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and Emotion Work in Lesbian, Gay, and Heterosexual Relationships

Abstract: Knowledge about how gender shapes intimacy is dominated by a heteronormative focus on relationships involving a man and a woman. In this study, the authors shifted the focus to consider gendered meanings and experiences of intimacy in same-sex and different-sex relationships. They merged the gender-as-relational perspective—that gender is co-constructed and enacted within relationships—with theoretical perspectives on emotion work and intimacy to frame an analysis of in-depth interviews with 15 lesbian, 15 gay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
134
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 33 publications
13
134
1
1
Order By: Relevance
“…Socially constructed gender differences within marriage contribute to disparities in emotion work (Erickson, 2005; Pfeffer, 2010; Umberson et al, 2015). Emotion work was first conceptualized by Arlie Hochschild (2003) as a component of both paid work outside the home (i.e., emotional labor) and unpaid work in the home (i.e., emotion work).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Socially constructed gender differences within marriage contribute to disparities in emotion work (Erickson, 2005; Pfeffer, 2010; Umberson et al, 2015). Emotion work was first conceptualized by Arlie Hochschild (2003) as a component of both paid work outside the home (i.e., emotional labor) and unpaid work in the home (i.e., emotion work).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Alongside other forms of unpaid work, including childcare and housework, emotion work is more often done by women compared to men and is often unacknowledged and invisible (Eichler & Albanese, 2007; Erickson, 2005). Emotion work can be a source of stress, particularly when it is unreciprocated and unappreciated and when it involves suppressing one’s own emotions (Umberson et al, 2015). For example, a person may act upbeat and happy while hiding his/her true feelings of anxiety and worry over a spouse’s depression in an effort to improve the spouse’s psychological state; this process may create stress and anxiety by increasing a sense of responsibility for the emotion worker (Thomeer, Umberson, & Pudrovska, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that women in both same-sex and different-sex relationships do more emotion work than men to allow and encourage the sharing of personal thoughts, feelings, and emotions between relational partners (Umberson, Thomeer, & Lodge, 2015). When men do engage in emotion work, they describe it in masculinized terms, similar to how they would describe themselves as financial providers (Thomeer, Reczek, & Umberson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of research has been conducted to look at emotion management and emotional labour in the context of organisations and the workplace (Zapf, 2002). The term 'emotion work' relates primarily to the private sphere and has been widely used within research on intimacy and personal relationships where the focus has been on relational emotion work, that done by one person for the benefit of another (for example Duncombe and Marsden, 1995;Erickson, 2005;Umberson et al, 2015). This paper considers the emotion management of personal emotions only, not interpersonal emotion management, in order to look at two types of work being done by the men in this research: the traditional work of constraining emotion, and the therapeutic work of disclosing emotion.…”
Section: Male Emotionality In Intimate Relationshipsmentioning
confidence: 99%